2008
DOI: 10.1007/s00428-008-0704-8
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic esophagitis in gastro-esophageal reflux disease: individual lesions, biopsy sampling, and clinical correlations

Abstract: Patients with non-erosive reflux disease may show microscopic damage. This study is aimed to describe distribution, sensitivity, and specificity of histological lesions (i.e., basal cell hyperplasia-BH, papillae elongation-PE, dilatation of intercellular spaces-DIS, intraepithelial eosinophils-IE, neutrophils, and erosions) and sampling criteria. Four groups were identified on the basis of symptoms, endoscopy, and pH monitoring: (1) erosive esophagitis (n = 48), (2) non-erosive esophagitis with abnormal pH (n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
61
1
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(67 citation statements)
references
References 27 publications
1
61
1
4
Order By: Relevance
“…5), and are scored using light microscopy based on the technique previously reported by Villanacci et al [23] and Mastracci et al [13]. Light microscopy has been shown to be equally as effective as electron microscopy for detecting DIS [24].…”
Section: Dilated Intercellular Spacesmentioning
confidence: 98%
See 3 more Smart Citations
“…5), and are scored using light microscopy based on the technique previously reported by Villanacci et al [23] and Mastracci et al [13]. Light microscopy has been shown to be equally as effective as electron microscopy for detecting DIS [24].…”
Section: Dilated Intercellular Spacesmentioning
confidence: 98%
“…Upper limit of basal cell layer = level above which the cell nuclei are separated by a distance greater than the nuclear diameter erosions) and dividing by the number of lesion types assessed [13]. In contrast with the images used in the evaluation of the draft criteria [12], the slides used in the current study were digitized whole slides that did not have the field of assessment indicated.…”
Section: Basal Cell Layer Hyperplasiamentioning
confidence: 99%
See 2 more Smart Citations
“…The criteria used for histological assessment of biopsy specimens were basal cell hyperplasia, papillae elongation, infiltration of neutrophils and eosinophils, dilatation of capillaries within papillae, and presence of dilated intercellular spaces (DIS) (7)(8)(9). The criteria were semiquantitatively scored as none, mild, medium, and severe on H&E-stained slides obtained from each biopsy site.…”
Section: Methodsmentioning
confidence: 99%